1999
DOI: 10.1074/jbc.274.43.30919
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Increases Rat Metalloproteinase-13 Gene Expression through Stimulation of Activator Protein 1 Transcription Factor in Cultured Fibroblasts

Abstract: The role of IL-6 in collagen production and tissue remodeling is controversial. In Rat-1 fibroblasts, we measured the effect of IL-6 on matrix metalloproteinase-13 (MMP-13), c-jun, junB, and c-fos gene expression, binding of activator protein 1 (AP1) to DNA, amount of AP1 proteins, immunoreactive MMP-13 and TIMP-1 proteins, and Jun N-terminal kinase activity. We show that IL-6 increased MMP-13-mRNA and MMP-13 protein. These effects were exerted by acting on the AP1-binding site of the MMP-13 promoter, as shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 73 publications
0
43
0
Order By: Relevance
“…Western Blot Analysis-Whole cellular protein extracts were prepared from HepG2 cells cultured until confluence as previously described (23).…”
Section: Methodsmentioning
confidence: 99%
“…Western Blot Analysis-Whole cellular protein extracts were prepared from HepG2 cells cultured until confluence as previously described (23).…”
Section: Methodsmentioning
confidence: 99%
“…Macrophage expression of MMP-13 can be stimulated by proinflammatory cytokines, including endothelial IL-6, which is strongly upregulated in the absence of NOS3, thereby promoting proinflammatory macrophage accumulation and increased macrophage-meditated MMP-13 expression, as detected, and as described in osteoblasts, 40 fibroblasts, 41 and cancer cells. High levels of MMP-13 were detected in carotid M1 infiltrated macrophages from patients undergoing carotid endarcterectomy, with extensive neointimal hyperplasia.…”
Section: Lavin Et Al Neointimal Formation Prevention By Enos 1745mentioning
confidence: 99%
“…Expression of MMP-13 can be controlled by a variety of stimuli including basic fibroblast growth factor (chondrosarcoma cells), inflammatory cytokines interleukin-1␤ (IL-1␤) and tumor necrosis factor-␣ (human chondrocytes), IL-1 (human chondrocytes), IL-6 (rat fibroblast), or TGF-␤1 and IL-1␤ (human fibroblast) (19,(27)(28)(29)(30)(31). Analysis of the MMP-13 gene revealed that its promoter region contains putative transcription factor binding sites containing TATA box, AP1, Polyomavirus enhancer activator-3 (PEA-3), osteoblast-specific element (OSE2), or AG-rich element (32).…”
mentioning
confidence: 99%